A compact printed ultra‐wideband multiple‐input multiple‐output prototype with band‐notch ability for WiMAX, LTEband43, and WLAN systems. Issue 6 (7th January 2019) - Biswal, Sonika Priyadarsini; Das, Sushrut
Abstract: A compact ultra‐wideband multiple‐input multiple‐output (UWB‐MIMO) antenna with good isolation and multiple band‐notch abilities is developed in this work. It consists of two quadrant shaped monopole antennas backed by ground stubs. A good isolation is achieved due to the two proposed extended curved ground stubs. The frequency rejection for the WLAN system is realized by loading a capacitive loaded loop resonator adjacent to the feed line. The band rejection for the WiMAX and LTE band43 system is achieved by embedding a quadrant shaped CSRR on each radiator's surface. The measured bandwidth of the antenna is 3.06 GHz‐11 GHz (|S11 | < −10 dB and |S21 | < −18 dB) with a band rejection from 3.5 GHz‐4 GHz to 5.1 GHz‐5.85 GHz, respectively. Time domain performances are investigated in terms of group and phase delay characteristics. Diversity characteristics are evaluated in terms of the envelope correlation coefficient, mean effective gain, and channel capacity loss.